High Incidence of Contact Dermatitis in Communal Rainwater Harvesting Users in a Rural Area of Sampang, Madura, East Java, Indonesia - Setyoningsih, Dian; Adriyani, Retno; Diyanah, Khuliyah Candraning; Elamin, Muhammad Zamzami (Tecno Scientifica Publishing, 2023)
Marparan village in Sampang, Indonesia uses a communal rainwater harvesting system (RWHS) for collecting water during the dry season. This study aimed to assess the quality of the water in the communal rainwater catchment pond (CRHP) and investigate the occurrence of contact dermatitis among the community members. The research followed an observational approach with a cross-sectional design, involving 50 individuals randomly selected from the user community of the CRHP for sanitation hygiene purposes. Water samples were collected from the CRHP and analyzed for physical characteristics, pH level, and surfactant content. The results revealed that the water in the communal rainwater storage pond did not meet the quality standards established by the Ministry of Health Indonesia. Additionally, a significant association was found between age and the occurrence of contact dermatitis. However, no significant relationships were observed between variables such as activity type, exposure frequency, and the incidence of contact dermatitis. Moreover, no relationships were identified between activity type, exposure frequency, duration of exposure, and the occurrence of contact dermatitis. It was observed that respondents did not rinse with clean water after using the communal rainwater storage pond for bathing or washing clothes. Therefore, it is recommended that individuals rinse with clean water after engaging in activities involving the use of the rainwater storage pond to minimize the risk of contact dermatitis.